Controlled acute trial of a thyrotrophin releasing hormone analogue (RX77368) in motor neuron disease. Issue 10 (October 1987) - Guiloff, R J; Eckland, D J; Demaine, C; Hoare, R C; MacRae, K D; Lightman, S L
Abstract : Twenty five patients with motor neuron disease completed a double blind randomised cross over trial of RX77368, a stabilised TRH analogue, iv over 2 hours against saline. Temporary improvement in bulbar symptoms including speech, respiratory parameters, tongue movements and swallowing were seen. Fasciculations increased and spasticity decreased. Change in muscle force with drug was different from placebo but both increase and decrease in force were seen and did not result in detectable changes in function. Side effects were clinically significant in 50% of the patients and cleared within 12 hours. Prolonged rise of thyroxine and an increase in plasma levels of prolactin, thyroid stimulating hormone and growth hormone were seen and followed characteristic patterns.